Emergency Department Burden of Gastroparesis in the United States, 2006 to 2013. Issue 2 (February 2019) - Hirsch, William; Nee, Judy; Ballou, Sarah; Petersen, Travis; Friedlander, Daniel; Lee, Ha-Neul; Cheng, Vivian; Lembo, Anthony
Abstract : Background and Aims: Gastroparesis, a chronic gastrointestinal disorder defined by delayed stomach emptying in the absence of obstruction, is often associated with frequent and costly visits to the emergency department (ED). The aim of this study was to analyze trends in gastroparesis-related ED visits from 2006 to 2013. Materials and Methods: Patients with a primary diagnosis of gastroparesis were identified from the Nationwide Emergency Department Sample (NEDS), the largest publicly available ED all-payer representative database in the United States. ED visits, admission rates, duration of hospitalizations, and charges were compiled. Patients with a secondary diagnosis of diabetes mellitus were analyzed as a subgroup. Results: The number of ED visits for gastroparesis as a primary diagnosis in the United States increased from 15, 459 in 2006 to 36, 820 in 2013, an increase from 12.9 to 27.3 per 100, 000 ED visits. The total charges associated with these ED visits and subsequent admissions increased from $286 million to $592 million. In contrast, admission rates through the ED decreased by 22%, procedure rates decreased by 6.2%, and the mean length of stay was shortened by 0.6 days. ED visits for patients with diabetic gastroparesis increased from 5696 to 14, 114, an increase from 4.7 to 10.5 per 100, 000 ED visits, with an increase in total associated charges for ED visits and subsequent admissions from $84 million to $182 million. Conclusions: The number of ED visits and associated charges for a primary diagnosis of gastroparesis with or without a secondary diagnosis of diabetes mellitus rose significantly from 2006 to 2013.